Frictional phenomena within a quasi zero stiffness vibration device - Shaw, A. D. (2024)
Quasi Zero Stiffness (QZS) devices have received widespread interest due to their potential applications in vibration isolation and as nonlinear energy sinks. However, as the stiffness is driven towards zero, the response becomes dominated by the effects of damping and friction. This places a strong emphasis on accurate modelling of these effects if realistic results are to be achieved. This work analyses and experimentally demonstrates the complex responses that can occur in a frictional QZS device, including isolated response regions and non-sinusoidal responses. This is done using a simple device recently developed by the authors that allows accurate adjustment of the nonlinear force–displacement curve. Furthermore, high frequency disturbances on the frictional system are shown to introduce a damping effect on the low frequency behaviour, and an equivalent linear damping coefficient is derived.